2010
DOI: 10.1016/j.foodres.2009.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nutritious acceptable snack bar using micronized flaked lentils

Abstract: Sixty-two women from 18 to 50 years of age who consume snack bars rated the acceptability of the six lentil snack bars and two commercial snack bars on a nine point hedonic scale from "dislike extremely" to "like extremely". Commercial snack bars on average were "liked moderately". Five of the six lentil snack bars were "liked slightly".Three lentil bars were found to be not significantly different from one of the commercial bars (p < 0.05). Purchase behaviour was measured on a seven point scale from "never" t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 24 publications
0
30
0
3
Order By: Relevance
“…Similarly, Ryland et al . () formulated a snack bar partially replacing oats with micronized flaked lentils (MFL), and they identified the sensory attributes that contribute to consumer acceptability. Three of six MFL formulations obtained high mean acceptability mean values, while external preference mapping determined that sweetness, grainy and lentil flavours, hardness, cohesiveness, cohesiveness of mass and moistness had the greatest influence on consumer acceptability.…”
Section: Lentil Protein and Food Applicationsmentioning
confidence: 99%
“…Similarly, Ryland et al . () formulated a snack bar partially replacing oats with micronized flaked lentils (MFL), and they identified the sensory attributes that contribute to consumer acceptability. Three of six MFL formulations obtained high mean acceptability mean values, while external preference mapping determined that sweetness, grainy and lentil flavours, hardness, cohesiveness, cohesiveness of mass and moistness had the greatest influence on consumer acceptability.…”
Section: Lentil Protein and Food Applicationsmentioning
confidence: 99%
“…Consumers have easily accepted cereal bars because they are believed to be a nutritionally balanced high-fibre snacks. Also, because they have an adequate balance between energy, fat, protein, vitamins, minerals, fibre and whole grains are beneficial to consumer health [8]. Lima [9] reported that the greatest challenge in obtaining a good cereal bar is a combination of many ingredients with main functionality like minerals, vitamins, proteins, fibres, binding agents and turns them into a product with flavor, aroma, texture and decent appearance, while trying to achieve specific goals nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have showed an extensive use of pulse proteins, such as lentils, peas, and chickpeas used to increase the biological value protein of cereal-based products (Han, Janz, & Gerlat, 2010;Ryland, Vaisey-Genser, Arntfield, & Malcolmson, 2010;Shirani & Ganesharanee, 2009). An interesting study aimed at examining changes in food consumption, satiety and perceived bowel health while consuming a diet rich in chickpeas was conducted by Murty, Pittaway, and Ball (2010).…”
Section: Introductionmentioning
confidence: 99%